Evaluation of Alexithymia, Somatosensory Sensitivity, and Health Anxiety Levels in Patients with Noncardiac Chest Pain - SÜNBÜL, MURAT (HINDAWI LTD, 2014)
Objective. Noncardiac chest pain (NCCP) is seen more frequently in young population and in these patients loss of function is evolving in social and professional areas. The aim of the study is to evaluate the levels of anxiety and somatic perception in patients with chest pain presenting to cardiology clinic. Methods. Fifty-one patients with noncardiac chest pain and 51 healthy controls were included in the study. All participants performed self-report based health anxiety inventory (HAI), somatosensory amplification scale (SAS), and Toronto alexithymia scale (TAS). Results. The patient group had significantly higher scores on the SAS, HAI-1, and HAI-T scales compared to controls (P < 0.001, P = 0.006, and P = 0.038, resp.). SAS, HAI-1, and HAI-T scores were significantly higher in female patients than male (P = 0.002, 0.036, and 0.039, resp.). There were significant differences in all TAS subscale scores between two groups. Patients, who had total TAS score more than 50, also presented higher levels of health anxiety (P = 0.045). Conclusions. Anxiety, somatic symptoms, and the exaggerated sense of bodily sensations are common in patients with NCCP. These patients unnecessarily occupy the cardiology outpatient clinics. These negative results can be eliminated when consultation-liaison psychiatry evaluates these patients in collaboration with cardiology departments.
Keywords: HEART-FOCUSED ANXIETY; PREDICTORS; SYMPTOMS; ANGINA; SCALE; CARE